A two parameter elasto-plastic formulation for hardening pressure-dependent materials. (October 2016) - Carollo, V.; Paggi, M.; Rossani, A.
Abstract : Highlights: A pressure-dependent yield function for hardening materials. Only two model parameters: the plastic Poisson ratio and a hardening parameter. Explicit closed-form expression of the flow rules and of the plastic multiplier. Abstract: A new pressure-dependent yield function is proposed by introducing a plastic Poisson's ratio within the theoretical formulation of the plastic potential. In analogy with other classical models, an equivalent stress and an equivalent plastic strain increment are defined. Then, according to these definitions, the equivalent stress–strain curve is derived and an exponential hardening law is introduced. The advantage of the proposed formulation over alternative approaches relies in explicit closed-form expressions of the flow rules and of the plastic multiplier.